Tempering temperature effect on the static and impact properties of 51CrV4 and 55Cr3 spring steels - Gülcan Toktaş; Adem Biçer (Materials Research Express)
This study investigated the impact of tempering temperature on the mechanical properties and microstructure of 51CrV4 and 55Cr3 spring steels, which are commonly utilized in the manufacturing of leaf springs. These springs are integral components of suspension systems in both land and railway vehicles. The steels were hardened through austenitizing at 870 °C for 30 min, followed by oil quenching. Subsequently, they were tempered at 300 °C, 375 °C, 450 °C, and 525 °C for 120 min. Mechanical testing (including hardness and tensile tests) and both micro and macrostructural analyses were carried out to assess the effect of tempering temperature. Additionally, impact tests at various temperatures were performed to evaluate the influence of tempering on ductile-to-brittle transition temperature (DBTT). X-ray diffraction was employed for phase analyses while scanning electron microscopy was utilized to examine fracture surfaces. The quenching/tempering processes resulted in strengths that were two to three times higher and lower hardening capacities below 0.05 in comparison to the normalizing treatment. The steels achieved their maximum ultimate tensile strengths above 1800 N mm ^−2 at 300 °C, with decreasing values as the tempering temperature increased. The hardness of 51CrV4 steel surpassed that of 55Cr3, attributed to the hardenability and precipitation-strengthening effects provided by the Cr and V content. Furthermore, impact energies increased with increasing testing temperatures (−40 °C, 0 °C, 25 °C, and +80 °C), with both steels tempered at 525 °C exhibiting higher and satisfactory impact energies across all testing temperatures, exceeding 15 J and 20 J, respectively. In addition, the tempered steels did not show a well-defined DBTT, while only the DBTT of normalized 51CrV4 steel was clearly determined at 0 °C.